PENGARUH MODEL PJBL TERHADAP KREATIVITAS SISWA MATERI IPAS HARMONI DALAM EKOSISTEM KELAS V SD NEGERI 20 SUNGAILIAT - Luciana Indriani Lusi; Yuanita; Said Akhmad Maulana (STKIP Subang, 2026)
This study was motivated by students’ low creativity, who tended to be passive andfound it difficult to generate ideas. It aimed to examine the influence of the ProjectBased Learning (PJBL) model on student creativity in the IPAS (Natural and SocialScience) material on Ecosystem Harmony in Grade V at SD Negeri 20 Sungailiat.This research employed a quantitative approach with a pre-experimental designusing a one-group pretest-posttest model. The sample consisted of one class of 20students selected through a saturated sampling technique. Data were collectedusing a questionnaire of 20 statements and observation sheets completed byobservers. Data analysis techniques included a normality test using the ShapiroWilk test and hypothesis testing using a paired sample t-test. The results showedthat the normality test using Shapiro-Wilk obtained significance values of 0.092 forthe pretest and 0.502 for the posttest, both greater than 0.05, indicating that the datawere normally distributed. The average pretest score was 47.25, and the posttestscore was 64.45. Hypothesis testing using the paired sample t-test yielded asignificance value of 0.000 < 0.05, indicating that H0 was rejected and Ha wasaccepted. It means that the PJBL model significantly influenced student creativity inthe IPAS material on Ecosystem Harmony in Grade V at SD Negeri 20 Sungailiat.